Role of neoblasts in the patterned postembryonic growth of the platyhelminth Macrostomum lignano. Issue 1 (1st January 2018) - De Miguel-Bonet, Maria Del Mar; Ahad, Sally; Hartenstein, Volker
ABSTRACT: Neoblasts are motile pluripotent stem cells unique to the flatworm phyla Platyhelminthes and Acoela. The role of neoblasts in tissue regeneration has received much attention in recent studies. Here we review data pertinent to the structure and embryonic origin of these stem cells, and their participation in normal cell turnover. Next, we present data proving that neoblasts also account for the addition of cells during postembryonic growth. Bromodeoxyuridine (BrdU) pulse chase experiments demonstrate that the incorporation of neoblast-derived cells into the different tissues of the juvenile worm follows a stereotyped pattern, whereby cells within the parenchymal layer (muscle, gland) incorporate new cells most rapidly, followed by the epidermal domain surrounding the mouth, dorsal epidermis, and, lastly, the nervous system.